Ultimate food journeys the world's best dishes & where to eat them - Abbott, Louise; Tomley, Sarah; Walisiewicz, Marek (Eyewitness travel, 2011)
"[A] book for food-lovers with an interest in travel--and ardent travelers with a passion for food. ... [also] has helpful sightseeing itineraries, hotel recommendations, and hundreds of restaurant choices"--P. [4] of cover.